PENGEMBANGAN MEDIA PERKULIAHAN PKN BERBASIS WEBSITE UNTUK MENINGKATKAN LITERASI BUDAYA DAN KEWARGAAN MAHASISWA PGSD UNIVERSITAS MUHAMMADIYAH SIDOARJO - Fihayati, Zuyyina; Macfhul Indrakurniawan; Ade Eviyanti; Nila Sekardhani Hadian; Septya Bayu Andita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop website-based Civics E-Book lecture media to improve the cultural and civic literacy skills of PGSD students of Muhammadiyah Sidoarjo University. This research was conducted based on the results of research conducted by researchers funded by DRPM Universitas Muhammadiyah Sidoarjo in the 2021/2022 fiscal year with the title "Cultural and Civic Literacy Abilities of PGSD UMSIDA Students in the 21st Century", where it was found that the cultural and civic literacy abilities of PGSD UMSIDA students of 68.4% had quite high cultural and civic literacy abilities. Based on this, eating needs to be improved so that the cultural and civic literacy skills of UMSIDA PGSD students become high, especially in Civic Education (Civics) lectures through a website-based Civics E-Book. The research is a Research and Development (R&D) research with the ADDIE version development model which is a synthesize of Analyze, Design, Development, Implementation, Evaluation.